Post-COVID-19 cardio-pulmonary manifestations after 1-year of SARS-CoV-2 infection among Indian population: A single centre, case-control study (OneCoV2 study) - Sumit Rajotiya; Shivang Mishra; Anurag Kumar Singh; Pratima Singh; Hemant Bareth; Mahaveer Singh; Preeti Raj; Deepak Nathiya; Balvir S. Tomar (Journal of Infection and Public Health, 2024)
Background: The evolving challenge of persistent symptoms post-Coronavirus disease-2019 (COVID-19), particularly debilitating cardio-pulmonary manifestations, necessitates further exploration. Our study aimed to assess the cardio-pulmonary complications in patients a year after hospital discharge from severe COVID-19, contrasting these with findings from a non-COVID group. Methods: The OneCoV2 study, a prospective, case-control study, was conducted at a tertiary care teaching hospital in northern India. We enrolled 43 subjects, with a mean age of 25.57 ± 7.94 years (COVID group) and 27.30 ± 8.17 years (non-COVID group). Comprehensive tests included pulmonary function tests, cardiac function tests, 6-min walk tests, and laboratory investigations. Results: Significant differences were found in the pulmonary function [forced vital capacity (FVC) (p = 0.037), forced expiratory flow (FEF) 25–75 % (p = 0.013)], and cardiac function [left ventricular ejection fraction (LVEF) (p = 0.032), heart rate (HR) (p = 0.047)], along with the six-minute walk test results between the two groups. In the COVID group, Pearson's correlation showed a negative correlation between FVC and C-reactive protein (CRP) [r = −0.488, p = 0.007] and a positive correlation between the six-minute walk test [r = 0.431, p = 0.003] and HR [r = 0.503, p = 0.013]. Conclusions: Our data suggest that pulmonary abnormalities are prevalent in COVID patients even after 1-year of hospital discharge. Cardiac biomarkers also show an inclination towards the COVID group. While we found significant correlations involving some parameters like FVC, CRP, HR, and results from the six-minute walk test, we did not find any significant correlations with the other tested parameters in our study.